HOUSEHOLD BUDGET PLANNING BASED ON DIGITAL FINANCIAL LITERACY PLATFORMS - Rahimov Doniyorbek Ollayorovich (Ecomind Press, 2026)
The effect of platforms aimed at increasing digital financial literacy on household budget formation and management is analyzed scientifically, theoretically and empirically. The study revealed the content of the concept of digital financial literacy and revealed the impact of mobile applications, online learning platforms and fintech services on household incomes, savings and expenditure structure. The results of the empirical analysis indicate that budget planning, savings share, and financial discipline improve as the degree of digital financial literacy increases. As a result of the research, scientific and practical recommendations were developed.
Keywords: Digital financial literacy, household budget, fintech, financial platforms, savings, income and spending.